Comparing Qurʾānic Suras with Pre-800 Documents - Kaplony, Andreas (Der Islam, 2018)
The dominant formal document type of preserved Arabic pre-800 documents shows a characteristic tripartite structure: in between the invocation and the long main part, there is a self-referring title hādhā kitāb min fulān ʾilà fulān, “The following is a writ from so-and-so to so-and-so.” The Suras of the Qurʾān have the same tripartite structure, but instead of the title can have one of six other options: an oath, a hymn, a reference to an eschatological event, an admonishment, a question, or a threat (or curse). We conclude that the Umayyad officials compiling the Qurʾān wrote the Qurʾān down as a collection of autonomous Suras. A close look at the major Qurʾānic terms used for God (allāh, rabb al-ʿālamīn, and al-raḥmān) and for Heaven and Hell shows a hegemonic terminology to be found in most Suras, and two minority terminologies – with which the Mysterious Letters are correlated – found in two groups of Suras only. We conclude that prior to the compilation of the Qurʾān, the mostly oral transmission of its texts allowed, if not encouraged, their wording to grow apart.